(untitled) (Journal of Asian Development Studies, 2015)
This study based on the empirical evidence on the impact of redistribution on inequality and growth in Pakistan. After doing a comprehensive literature review and by amplifying results from the empirical data from Pakistan in the period of 1990 to 2013, there is found a negative relationship between inequalities and growth in per capita. Redistribution assumed to be more in the societies where high inequality exists, but if we see in our study there is the stage where inequality is increasing over the last 30 to 40 years, GINI coefficient showed an increasing trend. This story took another root when money supply, trade openness, urbanization and tax collection also used in the model as control variables and tried as instruments for redistribution, and all are effecting growth in a significance and positive manor at the same time redistribution and inequality found negative determinants for per capita income in the 2SLS regression. Main point of our study is that our results have shown that redistribution is not significant measure for reduction in inequality however, over the last 30 years inequality is increasing rapidly and redistribution is also increasing in at low growth rates. And in case of Pakistan redistribution is effecting growth to negative same as inequality; the coefficients for redistribution and inequality are significantly negative. But this may be because of shorter time period of data is been used. In long run may be results come different in future studies.